Regional differences in the attitudes of veterinary students in Croatia towards welfare of farm and companion animals - Sabolek, Ivana (Array, 2020)
The aim of this study was to examine the attitudes of veterinary students in Croatia based on their home region towards the level of cognitive abilities and welfare in farm and companion animals. The survey encompassed 505 (91%) students of all six years of the integrated undergraduate and graduate study programme at the Faculty of Veterinary Medicine, University of Zagreb, Zagreb, Croatia. Student attitudes were examined through 17 statements using fivepoint Likert scale. The survey was focused on cattle, pigs, poultry, dogs and cats. The results obtained revealed that students from Zagreb and central Croatia expressed significantly higher attitudes (P<0.05) towards the level of thought process in cattle, pigs, dogs and cats, and the level of welfare in pigs than students from eastern Croatia and Dalmatia. Foreign students expressed the highest level of concern about the welfare of laying hens, and the lowest about the welfare of dogs and cats. Students from Lika and Gorski Kotar expressed the highest level of concern about the welfare of dogs and cats. No regional differences were determined in student attitudes towards the level of emotions in the observed species. The study results confirmed the existence of regional differences in the attitudes of Croatian veterinary students towards the welfare of farm and companion animals. The findings suggest that these differences may not only be the result of cultural differences among Croatian regions, but veterinary students may also increasingly encounter welfare issues in certain regions, especially in the case of companion animals.